Reaching experts for enhanced referral (REFER) to pain psychology: a modified Delphi approach with multidisciplinary paediatric pain providers at a specialised center in the USA - Laura E Simons; Lauren E Harrison; Nicole Jehl; Lea Schemer; Courtney W Hess; Alexandra J Neville; Ryan S L Ma; Julia A Glombiewski (BMJ Paediatrics Open)
Background To minimise the referral gap to pain psychology, the purpose of this study was to describe clinician-perceived patient suitability for pain psychology referral, develop a referral plan and outline essential elements of a referral conversation via a modified Delphi approach with multidisciplinary paediatric pain providers.Methods We employed a three-round modified Delphi approach consulting multidisciplinary paediatric pain providers (n=18) including physicians, psychologists, physical therapists, occupational therapists and nurse practitioners (PT, OT, NP). Based on the responses to an online survey (Round 1), initial statements regarding the pain psychology referral process were developed. These statements were revised in three separate panels (MD panel, PSY panel, PT, OT, NP panel; Round 2). A priori consensus criteria were verified for each statement within and between groups using anonymous responses to a concluding online survey (Round 3).Results Approximately one-third of the statements (35%) reached consensus across all panels. For example, paediatric pain providers agreed that referrals should be communicated verbally, along with written materials, and that pain should be explained early from a biopsychosocial perspective. Paediatric pain providers also suggested minimising barriers through a flexible, stepped-care approach that adapts the delivery of pain psychology beyond traditional models. However, most statements reached consensus in only one or two panels (52%), indicating a lack of consensus across disciplines. The data suggest that it was comparatively easier to reach an overall consensus on statements formulating an ideal referral process to pain psychology (50%) than on statements characterising patient suitability (13%).Conclusions Paediatric pain providers developed an actionable plan for pain psychology referrals. This plan could bridge referral gaps and improve access to pain psychology treatment. Given the low provider consensus on patient suitability, further research is warranted to understand pain psychology referral decision-making, including differing perceptions of patient suitability across disciplines.